Effects of frequent hemodialysis on blood pressure: Results from the randomized frequent hemodialysis network trials. Issue 3 (5th January 2015) - Kotanko, Peter; Garg, Amit X.; Depner, Tom; Pierratos, Andreas; Chan, Christopher T.; Levin, Nathan W.; Greene, Tom; Larive, Brett; Beck, Gerald J.; Gassman, Jennifer; Kliger, Alan S.; Stokes, John B.; et al.
Abstract Hypertension is a common complication of chronic kidney disease and persists among most patients with end‐stage renal disease despite the provision of conventional thrice weekly hemodialysis (HD). We analyzed the effects of frequent HD on blood pressure in the randomized controlled Frequent Hemodialysis Network trials. The daily trial randomized 245 patients to 12 months of 6× ("frequent") vs. 3× ("conventional") weekly in‐center hemodialysis; the nocturnal trial randomized 87 patients to 12 months of 6× weekly nocturnal HD vs. 3× weekly predominantly home‐based hemodialysis. In the daily trial, compared with 3× weekly HD, 2 months of frequent HD lowered predialysis systolic blood pressure by −7.7 mmHg [95% confidence interval (CI): −11.9 to −3.5] and diastolic blood pressure by −3.9 mmHg [95% CI: −6.5 to −1.3]. In the nocturnal trial, compared with 3× weekly HD, 2 months of frequent HD lowered systolic blood pressure by −7.3 mmHg [95% CI: −14.2 to −0.3] and diastolic blood pressure by −4.2 mmHg [95% CI: −8.3 to −0.1]. In both trials, blood pressure treatment effects were sustained until month 12. Frequent HD resulted in significantly fewer antihypertensive medications (daily: −0.36 medications [95% CI: −0.65 to −0.08]; nocturnal: −0.44 mediations [95% CI: −0.89 to −0.03]). In the daily trial, the relative risk per dialysis session for intradialytic hypotension was lower with 6×/week HD but given the higher number of sessions per week, there was a higher relative risk for intradialytic hypotensive requiring saline administration. In summary, frequent HD reduces blood pressure and the number of prescribed antihypertensive medications.